Is breastfeeding associated with later child eating behaviours?. (1st July 2020) - Pang, Wei Wei; McCrickerd, Keri; Quah, Phaik Ling; Fogel, Anna; Aris, Izzuddin M.; Yuan, Wen Lun; Fok, Doris; Chua, Mei Chien; Lim, Sok Bee; Shek, Lynette P.; Chan, Shiao-Yng; Tan, Kok Hian; et al.
Abstract: Individual differences in children's eating behaviours emerge early. We examined the relationship between breastfeeding exposure and subsequent eating behaviours among children from the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort. Children (n = 970) were grouped according to their breastfeeding exposure: high (full breastfeeding ≥ 4 months with continued breastfeeding ≥ 6 months), low (any breastfeeding < 3 months or no breastfeeding) and intermediate (between low and high breastfeeding categories). Aspects of eating behaviour from ages 15 months to 6 years were captured using a combination of maternal reports (Child Eating Behaviour Questionnaire; Infant Feeding Questionnaire; Preschooler Feeding Questionnaire) and laboratory-based measures of meal size, oral processing behaviours (e.g. average eating speed and bite size) and tendency to eat in the absence of hunger. Most children had low (44%) or intermediate (44%) breastfeeding exposure; only 12% had high exposure. After adjusting for confounders, multivariable linear regression analyses indicated the high (but not intermediate) breastfeeding group was associated with significantly lower reported food fussiness at 3 years compared to low breastfeeding group (−0.38 [-0.70, −0.06]), with similar but non-significant trends observed at 6 years (−0.27 [-0.66, 0.11]). At 3 years, mothers in the high breastfeeding group also reported the least difficulty in child feeding compared to low breastfeeding group (−0.22 [-0.43, −0.01]). However, high breastfeeding was not associated with any other maternal-reports of child feeding or eating behaviours, and no significant associations were observed between breastfeeding exposure and any of the laboratory measures of eating behaviour at any of the time points. These results do not strongly support the view that increased breastfeeding exposure alone has lasting and consistent associations with eating behaviours in early childhood.